INDIGENOUS BACTERIAL DIVERSITIES IN TWO AGRICULTURAL SOILS AS INFLUENCED BY CHEMICAL AND ORGANIC HERBICIDES (2024)
Agricultural soils as habitats for beneficial soil bacteria are usually invaded by weeds, an occurrence which has detrimental effects on crops. Chemical herbicides mostly employed for weed control adversely affect soil bacteria. Previous studies have reported chemical herbicides’ effects on soil bacterial diversity suppressing microbial growth, however, information on soil types, and organic herbicides that could be an alternative is limited. Therefore, this study was designed to investigate the effects of chemical and organic herbicides on bacterial diversity in Alfisol and Inceptisol. Soils (Alfisol and Inceptisol) were collected from research farms at University of Ibadan, Institute of Agricultural Research and Training, National Horticultural Research Institute, and International Institute of Tropical Agriculture. In a screen house experiment using a factorial arrangement in a completely randomised design, Atrazine and S-Metolachlor (AS-M), Isopropyl Amine (IA), and Acetic Acid (AA) herbicides were applied as pre-, post- and organic herbicides, respectively on the soils. In the field experiments, AS-M, IA and AA herbicides were also applied to the Alfisol and Inceptisol. All herbicide-treated soils were sampled at 4 and 8 weeks and bulked to determine physico-chemical parameters and herbicides persistency of the treated and untreated soils using standard methods. The effect on bacterial diversity in herbicide treated Alfisol and Inceptisol were determined by DNA extraction from the soil samples using 16S rRNA amplicons sequenced on illumina miseq. Data were analysed using descriptive statistics, QIIME 2, and ANOVA at α0.05. Untreated Alfisol pH (6.20±0.12), organic carbon (3.90±0.04g/kg) and clay content (112.20±0.55g/kg) were significantly higher than Inceptisol pH (5.50±0.15), organic carbon (1.90±0.01g/kg) and clay content (103.90±0.81g/kg). At week 4, pH and organic carbon were significantly higher in Alfisol (6.30±0.21: 0.40±0.06g/kg) than Inceptisol (5.40±0.21; 0.10±0.06g/kg). Herbicides’ persistency was higher in Alfisol than Inceptisol. Intermediate products (acetamide) in AA-treated soil (Alfisol: 30.2%; Inceptisol: 25.0%) < 2-amino-3-4- dihydro-4-4-dimethyl-6-pyrimidinone (Alfisol: 48.7%; Inceptisol: 35.3%) in IA < atrazine (Alfisol: 50.9%; Inceptisol: 37.1%) in AS-M at week 4, with a similar trend Alfisol: 22.1%, Inceptisol: 19.2%; Alfisol: 42.6%, Inceptisol: 33.2%; Alfisol: 43.9%, Inceptisol: 35.1% at week 8. Alfisol had significantly higher bacteria taxa of 79% than 21% in Inceptisol. Methylomicrobium, Saccharopolyspora, Domibacillus, Blatococcus, Fuctibacillus, Limnobacter, Sneathiella, Nocardiopsis, Aquisphaera, and Stenotrophomonas were found in Alfisol and Inceptisol. However, Limnobacter and Methylomicrobium; Sneathiella and Nocardiopsis; Aquisphaera and Saccharopolyspora; were the bacterial genera that survived in AS-M, IA and AAtreated-soils, respectively. Significant effect in relative abundance of bacterial genera Chthoniobacter (Alfisol: 0.5%, 0.4%, 0.3%, 0.6%: Inceptisol: 0.3%, 0.2%, 0.3%, 0.5%) and Pedosphaera (Alfisol: 0.6%, 0.6%, 0.5%, 0.9%, Inceptisol: 0.7%, 0.5%, 0.5%, 0.9%) were observed at week 4, Chthoniobacter (Alfisol: 0.5%, 0.4%, 0.4%, 0.6%: Inceptisol: 0.3%, 0.3%, 0.4%, 0.5%) and Pedosphaera (Alfisol: 0.6%, 0.8%, 0.5%, 0.9%, Inceptisol: 0.3%, 1.2%, 0.9%, 1.3%) at week 8 in untreated and soil treated with AS-M, IA and AA, respectively. Alpha and beta diversity indicated significant differences in the relative abundance of bacteria between Alfisol and Inceptisol. The relative abundance of bacteria diversity in Alfisol and Inceptisol were reduced by chemicals but increased by organic herbicides